Analysis of the Effect of Financial Literacy and Financial Technology on the Sustainability of Micro, Small and Medium Enterprises (MSMEs) in the Tourism Village of Kota Pari Mangrove Forest, Pantai Cermin District - Geby Citra Ananda; Maya Syaula; Zuhri Ramadhan; Agung Sahputra (International Journal of Management, Economic and Accounting, 2024)
The problem that occurs in the Kota Pari Village community is the lack of knowledge related to finance, especially in terms of Financial Literacy and Financial Technology. Financial Literacy is very important in everyday life. The higher the level of financial literacy in each individual, it will encourage an increase in financial performance. Entering the industrial revolution 5.0, many challenges and opportunities are presented. One of them is the existence of innovations in the financial sector, namely Financial Technology (Fintech). Fintech is present with the aim of facilitating services for the community to carry out economic activities more effectively and efficiently. The purpose of this study was to analyze the effect of Financial Literacy and Fianncial Technology (Fintech) on the business sustainability of micro, small and medium enterprises (MSMEs) in Kota Pari Village. The population in this study were all MSMEs in Kota Pari Village. The success of this implementation is expected to have a positive impact on the economic development and welfare of the Kota Pari Village community.